Innovations in practice: Adaptation of developmental and behavioral pediatric service in a tertiary center in Singapore during the COVID-19 pandemic - Kalyani Vijaykumar Mulay; Ramkumar Aishworiya; Tammy S.H. Lim; Mae Yue Tan; Jennifer S.H. Kiing; Shang Chee Chong; Ying Qi Kang (Elsevier, 2021)
Background: As the coronavirus 2019 pandemic continues, healthcare services need to adapt to continue providing optimal and safe services for patients. We detail our adaptive framework as a large Developmental and Behavioral Pediatrics service in a tertiary academic institution in Singapore. Methods: The multidisciplinary team at our unit implemented various adaptations and workflow processes during this evolving pandemic in providing continued clinical care tailored to the challenges specific to our patient population. Services were continued via teleconsultation mode during the 'Circuit Breaker' (enhanced movement restriction) period. Specific workflow processes, IT infrastructure, and staff training were put in place to support smooth running of this service. Segregation of services into two teams based at two separate sites and implementation of stringent infection control measures surrounding the clinic visit by providers, patients and their families were incorporated to ensure safety. Measures were also taken to ensure providers' mental wellbeing. Results: The clinical service was continued for the majority of our patients with a lowest reduction in patient consultations to half of baseline during the 'Circuit Breaker' period. We received positive feedback from families for teleconsultation services provided. Conclusion: We have been able to continue services in our DBP clinics due to our dynamic reassessment of workflow processes and their prompt implementation in conjunction with the hospital and national public health response to the pandemic. Given that this pandemic is likely to be long drawn, our unit remains ready to constantly adjust these workflows and make adaptations as we go along, together with the support for mental health of patients, parents and staff. Continual improvements in workflows will be helpful even beyond the pandemic to ensure good continuity of care for our patients and families.